Investigating the effectiveness of emotion regulation-based treatment on worry, emotion regulation and psychological flexibility in patients with generalized anxiety disorder: a case study - Sadeghi, Saeideh; Foroughi, Aliakbar; Ahmadi, Seyed Mojtaba (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Generalized anxiety disorder is a disorder with comparable functional impairment to major depression and a poorer quality of life than major depression. Therefore, the present study was conducted with the aim of investigating the effectiveness of an emotion regulation-based treatment on emotion regulation, psychological flexibility, and the experiences of patients with generalized anxiety disorder. Materials and Methods: The study was carried out in the form of a case study with 5 patients with generalized anxiety disorder. The treatment consisted of 12 90-minute sessions and was carried out individually. Questionnaires on Difficulty in Emotion Regulation Scale (DERS), Acceptance and Commitment Questionnaire (AAQ) and Penn State Worry Questionnaire (PSWQ) were used to measure outcome variables. Results: The results showed that according to visual analysis of data graphs and descriptive statistics index, the intervention was effective for each of the five subjects. Conclusion: Based on these findings, it can be concluded that emotion regulation-based treatment is a useful strategy for enhancing psychological flexibility, anxiety, and emotion regulation in patients with generalized anxiety disorder. It can also be concluded that deficiencies in these areas are a significant contributing factor to the development of generalized anxiety disorder.